Konsep dan Praktik Pelaksanaan Amicus Curiae Dalam Sistem Peradilan Pidana Indonesia - Sukinta Sukinta (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2021)
AbstractAmicus Curiae is a common practice in the Common Law legal system. Amicus Curiae or friends of court is a legal concept that supports third parties, namely those who feel an interest in a case, giving their legal opinion to the court. This study aims to determine how the concept and practice of amicus curiae in the Indonesian criminal justice system. This research is an empirical legal research that uses a case approach approach. The results showed that Amicus Curiae or court friend or court friend is a legal concept that supports third parties, namely those who feel interested in a case, giving their legal opinion to the court. The involvement of interested parties in a case is only limited to giving opinions, not fighting. Amicus Curiae is a practice that originates from the Roman legal tradition which later developed and was practiced in the common law legal system. The concept of Amicus Curiae used in the Indonesian legal system is based on the provisions of Article 5 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power which states that